Respons Karakter Agronomi pada Tanaman Jagung (Zea mays) Varietas Pioneer 36 Akibat Aplikasi berbagai Teknik Pengendalian Organisme Pengganggu Tumbuhan - Ardian, Fahmi; Afifah, Lutfi; Sugiarto, Sugiarto; Prabowo, Dwi Priyo; Irfan, Budi; Widiawan, Aditia Bagus (UNIVERSITAS LABUHANBATU, 2022)
The application of plant pest management techniques can affect agronomic character of crops, because there are active ingredients that acts as biofertilizer and biostimulant. This study aims to obtain the best agronomic character as a result the application of various active ingredientson corn crops (Zea mays) of the variety of Pioneer 36. The research method used was an experimental method, with a single-factor group randomize design, consisting of 4 treatments and 6 replications. The treatments of plant pest management consists of control (C), combination management (CM) a.i. PGPR, macro nutrient and micro nutrient; biointensive management (BM) a.i. Trichoderma hamatum and rice husk ash; synthetic management (SM) a.i. pyraclostrobin. The data obtained were analyzed variance and if the results were significantly different, it was followed by the least significant difference (LSD) at the level of 5%. The results showed that, the CM treatments gave the highest results on plant height (10,66 cm-248,78 cm) and the number of rows per cob (14,18). Meanwhile, the SM treatments gave the highest results on the length of cob without corn husk (17,44 cm) and the diameter of cob without corn husk (4,13 cm).Key words: PGPR, Trichoderma hamatum, rice husk ash, pyraclostrobin.